Further Research on the Proofs of the Permissibility of the Wifeâs Appropriation in Bridal Gift Prior to Establishment - Ã˜Â§Ã˜ÂÃ˜Â¯Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ™Â Ã˜Â§Ã™Â„Ã™Â‡; Ã™ÂÃ˜Â®Ã™Â„Ã˜Â¹Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã˜ÂªÃ™Â‚Ã›ÂŒ; Ã˜ÂÃ˜Â§Ã˜Â¦Ã˜Â±Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã˜ÂÃ˜Â³Ã™Â† (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Upon conclusion of marriage contract, the wife becomes the owner of all the mahr (bridal gift). This ownership is established for half of the mahr and unestablished (mutizalzil) for the other half and she will get the right to own all of it by self-submission. The important issue to be brought up here is the permissibility or impermissibility of the wifeâs appropriations in the mahr prior to its establishment. The jurists and legal experts have maintained the permissibility of the appropriations without separation of the discourse in different modes after the wifeâs attaining ownership, according to the general proofs denoting the permissibility of the proprietor in his/her property and the traditions denoting the wifeâs permissibility of appropriation related to the husband. In a descriptive-analytical method and by delving into the juristsâ proofs and phrases and viewing the general proofs as violable, the writers of this paper have deemed as sound only the wifeâs appropriations related to the husband as well as the appropriations permitted by the husband; otherwise, they have found her appropriations impermissible due to the unestablishment of the wifeâs ownership of half of the mahr and in order to observe the husbandâs right.